(untitled) (Academia Science Repository, 2023)
Physical culture training, which is a component of the education and training system, has its significance in ensuring the comprehensive and active development of members of society. Taking this into account, special attention is paid to improving the physical culture of citizens in our country. This article will conduct some research on modern trends in the development of the physical culture of primary school pupils.